Considerations on the use of cast-in-place piles in permafrost - Weaver, J. S.; Morgenstern, N. R. (Canadian Geotechnical Journal, 1980)
Conventional cements have proven to be unsuitable for subsurface concreting in permafrost and as a result cast-in-place piles have seldom been used in arctic regions. The petroleum industry has developed a gypsum-based cement that has been satisfactorily used to grout well casings through permafrost.Laboratory studies have been undertaken to evaluate the suitability of this cement for subsurface concreting in permafrost. It is concluded that this cement does have an adverse effect on the adfreeze bond strength and hence should not be used for cylindrical friction piles. However, it appears from this preliminary study that the cement does have potential for use as a construction material for cast-in-place belled and tapered piles.